A fast parallel SC-Fano decoding algorithm for PAC codes - Wu, Yunzhi; Li, Li; Fan, Pingzhi (Science China. Information sciences, 2023)
In order to effectively reduce the “decoding latency” of successive cancellation decoding aided Fano (SC-Fano) decoder employed in polarization-adjusted convolutional (PAC) codes, a fast parallel SC-Fano decoding algorithm is designed, which leverages multiple individual decoding components. Critical challenges arise from how to appropriately initialize the thresholds of different SC-Fano decoding components and how will these decoding components cooperate with each other. After appropriately overcoming these challenges, our design is capable of halving the “decoding latency” without incurring any noticeable frame error rate (FER) performance degradation, meanwhile, the overall computational complexity is normally constrained below one and a half times of that required by conventional SC-Fano decoders in simulated typical configurations.